2019
DOI: 10.3390/v11100886
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Pathogenesis: From Early Case Reports to Epidemics

Abstract: For the first 60 years following its isolation, Zika virus (ZIKV) remained a relatively poorly described member of the Flaviviridae family. However, since 2007, it has caused a series of increasingly severe outbreaks and is now associated with neurological symptoms such as Guillain-Barré syndrome and congenital Zika syndrome (CZS). A number of reports have improved our understanding of rare complications that may be associated with ZIKV infection in adults, the areas of the body to which it spreads, and viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
(121 reference statements)
0
14
0
Order By: Relevance
“…We observed ZIKV-associated dysmyelination within such cultures and determined that the key CNS myelinating cell type, oligodendrocytes, are predominant targets for ZIKV [ 44 ]. The causal link between GBS, a PNS neuropathy, and ZIKV infection in a predominantly demyelinating subtype of the disease is well established [ 12 , 19 , 45 , 85 , 86 ]. Although our prior studies on murine PNS myelinating cultures infected with ZIKV show poor infection of the myelin-forming Schwann cells in the PNS [ 44 ], others have shown that ZIKV infection caused cytopathic effects in Schwann cells resulting in PNS myelin degeneration [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed ZIKV-associated dysmyelination within such cultures and determined that the key CNS myelinating cell type, oligodendrocytes, are predominant targets for ZIKV [ 44 ]. The causal link between GBS, a PNS neuropathy, and ZIKV infection in a predominantly demyelinating subtype of the disease is well established [ 12 , 19 , 45 , 85 , 86 ]. Although our prior studies on murine PNS myelinating cultures infected with ZIKV show poor infection of the myelin-forming Schwann cells in the PNS [ 44 ], others have shown that ZIKV infection caused cytopathic effects in Schwann cells resulting in PNS myelin degeneration [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…These included neurodevelopmental impairments, grouped under the description “congenital Zika syndrome” (CZS), as well as fetal death. Moreover, later neurodevelopmental abnormalities have been reported, thus emphasizing the need for long-term surveillance [ 3 , 4 , 6 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The full spectrum of disease may indeed only become clear over time.…”
Section: Introductionmentioning
confidence: 99%
“…West Nile virus (WNV) and Zika virus (ZIKV) are medically important arboviruses that cause severe neurological disease in humans [ 23 , 24 ]. Control of WNV requires robust neuroinflammation and infiltration of peripheral leukocytes into the central nervous system (CNS), mediated by RIPK1 and RIPK3 [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2015 ZIKV outbreak was considered as a test case in the context of the PREPARE network, as the pathogenesis of neurologic or immune disease induced by ZIKV is not fully understood. ZIKV is a flavivirus belonging to the Flaviviridae family and had only marginally been researched prior to the 2015 epidemic was minimal (68). Outbreaks of ZIKV disease have been recorded in Africa, the Americas, Asia and the Pacific.…”
Section: Introductionmentioning
confidence: 99%